A high-performance supercapacitor electrode based on tremella-like NiC2O4@NiO core/shell hierarchical nanostructures on nickel foam. Issue 6 (19th January 2017) - He, Dong; Liu, Guolong; Pang, Anqi; Jiang, Yang; Suo, Hui; Zhao, Chun
Abstract : Tremella-like nickel oxalate@nickel oxide (NiC2 O4 @NiO) core/shell hierarchical nanostructures have been successfully synthesized on nickel foam through a facile hydrothermal method followed by an electrochemical activation process. Abstract : Tremella-like nickel oxalate@nickel oxide (NiC2 O4 @NiO) core/shell hierarchical nanostructures have been successfully synthesized on nickel foam, using Ni foam as a current collector, a Ni source and a three-dimensional (3D) substrate, through a facile hydrothermal method followed by an electrochemical activation process. The prepared samples can be directly used as binder-free electrodes for supercapacitors. The tremella-like morphology, together with the NiC2 O4 nanoblocks on 3D Ni foam, significantly increases the amount of active sites for redox reactions and the conductivity of the electrode material, shortens the diffusion pathway for ions, facilitates the effective penetration of the electrolyte, and lowers the intrinsic equivalent series resistance, demonstrating good potential for energy storage application. This material has a high specific capacitance of 2287.09 F g −1 at 1 A g −1, a good cycling stability (remaining 95% after 10 000 cycles) and a good rate capability (83.2% retention upon increasing the current density by 10 times).